Length-weight relationship and biometry of the groupers Epinephelus tauvina (Forsskal, 1775) andÂ£^. malabaricus (Schneider, 1801) - Shanmugam, A; Soundarapandian, P; Pramod, G; Kannupandi, T (Indian Journal of Fisheries, 2011)
The parabolic equation W = aL" was used to study the length-weight relationship of Epinephelus tauvina and E. malabaricus. The ’r’ value for E. tauvina and E. malabaricus was found to be 0.9097 and 0.9559 and the regression equation Log W = -4.756 + 2.986L and Log W = -4.8680 + 2.6216L respectively. Analysis of covariance showed significant difference between E. tauvina and E. malabaricus in their length-weight relationship (F=8.3529). Further the allometric relationship between the morphometric characters was studied by using the equation Y = a+bx. Both positive and negative allometry was observed in the biometric analysis whereas no isometry was observed